Dietary fatty acids and chylomicron synthesis and secretion. (1st February 2004) - Williams, C.M.; Bateman, P.A.; Jackson, K.G.; Yaqoob, P.
Abstract : There is currently considerable interest in potential atherogenic and thrombogenic consequences of elevated concentrations of triacylglycerols, especially in the post-prandial state. Despite this, there is limited information on the effects of dietary fatty acids on the synthesis, secretion and metabolism of chylomicrons, the large triacylglycerol-rich lipoproteins synthesized in the enterocyte following the digestion and absorption of dietary fat. This brief review considers current approaches to the investigation of chylomicron synthesis and summarizes some of the human, cell and animal studies that have investigated effects of different fatty acids on these pathways. Potential sites for modulatory effects of dietary fatty acids on the molecular events of chylomicron synthesis are proposed in the light of the recent model that has been developed from cell and animal studies and observations based on abnormalities in chylomicron formation in human inherited autosomal recessive diseases.